2019
DOI: 10.3390/antiox8090362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tannase and Ultrasound Treatment on the Bioactive Compounds and Antioxidant Activity of Green Tea Extract

Abstract: The present study investigated the effects of tannase and ultrasound treatment on the bioactive compounds and antioxidant activity of green tea extract. The single-factor experiments and the response surface methodology were conducted to study the effects of parameters on antioxidant activity of green tea extract. The highest antioxidant activity was found under the optimal condition with the buffer solution pH value of 4.62, ultrasonic temperature of 44.12 °C, ultrasonic time of 12.17 min, tannase concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 60 publications
4
33
0
Order By: Relevance
“…HTs contains mainly glucogallin, gallotannins, ellagitannins, and their derivatives (39). Tannase (a glycoprotein esterase) hydrolyzes GA from gallotannins, thereby increasing available GA absorbed in the gastrointestinal tract (GIT) (40,41). The GA groups are usually bonded to form dimers, such as ellagic acid.…”
Section: Physicochemical Properties Of Gamentioning
confidence: 99%
“…HTs contains mainly glucogallin, gallotannins, ellagitannins, and their derivatives (39). Tannase (a glycoprotein esterase) hydrolyzes GA from gallotannins, thereby increasing available GA absorbed in the gastrointestinal tract (GIT) (40,41). The GA groups are usually bonded to form dimers, such as ellagic acid.…”
Section: Physicochemical Properties Of Gamentioning
confidence: 99%
“…However, these traditional methods have the disadvantages of the large consumption of organic solvent, long extract time and low efficiency [12,13]. Therefore, some new extraction methods came into being to overcome these problems, including ultrasound-assisted extraction, pressurized liquid extraction, enzyme-assisted extraction and microwave-assisted extraction (MAE) [14][15][16]. Microwave-assisted extraction has been applied in the extraction of some plant active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…However, the TAN group showed a negative effect on CAT activity compared with the GTE group. This is because tannase might induce the degradation of some related bioactive compounds [71]. Seen from Figure 1B, although the activity of SOD in the UST group was significantly higher than that of the GTE group, all treatment groups did not increase SOD activity compared with the model group.…”
Section: Effects Of Extracts On Antioxidant Enzymes Gsh and Mda In mentioning
confidence: 91%
“…In our previous study, the treated extracts showed stronger in vitro antioxidant activities than the original extracts, and the contents of several compounds were determined using the HPLC method [71]. HPLC results revealed that tannase and ultrasound treatment increased gallic acid content, while the original extract had a higher EGCG content than the treated extracts.…”
Section: Effects Of Extracts On Tg In Livermentioning
confidence: 96%
See 1 more Smart Citation